Comparing the Expression of Estrogen Receptors, Progesterone Receptors, and Human Epidermal Growth Factor Receptor 2 Between Initial Biopsy and Excision Specimens in Invasive Breast Carcinoma Cases. Is There a Need for Universal Repeat Testing? Experience From a Community Hospital - Astrid M Sacasa; Gul Emek Wymer; Susana Ferra (HCA Healthcare Journal of Medicine, 2026)
Background The current national recommendation is that breast biomarkers estrogen receptors (ER), progesterone receptors (PR), and human epidermal growth factor receptor 2 (HER2) testing should be done on all primary invasive breast carcinomas and on recurrent or metastatic tumors. Repeat testing on a subsequent excision specimen is not indicated unless results appear discordant with the histopathologic findings. The objective of the current study was to evaluate the need for adopting universal reflex re-testing of breast biomarkers in excision specimens in our institution. Methods The study population included 70 sequential invasive breast cancer patients where the results of ER, PR, and HER2 in the initial diagnostic biopsy were available for comparison with our repeated ER, PR, and HER2 testing in the resection specimens. We aimed to identify if there are a significant number of discordant cases and if there are any significant tumor variables (size, ductal carcinoma in situ [DCIS], nodal [N] stage, neoadjuvant therapy) in the discordant cases. Results Of the 70 patients, 10 (14%) had discordant results. Seventeen (24.3%) received neoadjuvant therapy. The discordance rate was 7.5% in the control (non-neoadjuvant therapy) group and 35.3% in the neoadjuvant therapy group (P = .0091). Three (37.5%) patients with hormone receptor-positive results became excision negative. Two (50%) biopsy HER2 positive patients became excision negative, and 5 (7.6%) biopsy HER2 negative patients became excision positive. Additionally, a tumor size greater than 2 cm was significantly associated with a higher discordance rate (P = .0082). Conclusion Adopting universal reflex re-testing of breast biomarkers in all excision specimens is not justified by our results. Our center will implement reflex re-testing as the new standard of care for all post-neoadjuvant therapy cases, as well as for tumors measuring greater than 2 cm.